Effect of montelukast as monotherapy in mild persistent asthma - Senthilvelan, Bharathi; Gopalakrishnan, Harini; Kunchithapatham, Muthukumar (International Journal of Research in Medical Sciences, 2017)
Background: Leukotriene Receptor Antagonists (LTRAs) have a role in moderate and severe persistent asthma as a steroid sparing agent. The role of these agents as monotherapy in mild persistent asthma still needs to be determined. Montelukast is FDA approved for use in children >1 year of age. This study was done to assess the effect of montelukast as monotherapy in children with mild persistent asthma. Methods: A prospective interventional study was conducted in Department of Pediatrics in Chennai Medical College Hospital and Research centre, Trichy, India from June 2014 to August 2015. A 12 week interventional trial to compare the effect of montelukast with placebo in children with mild persistent asthma and 6 months follow up of cases and controls. The assessment was done by clinical scoring and peak expiratory flow rate (PEFR). Results: At the end of 12 weeks therapy and at 3 months follow up symptom control was significant in the montelukast group. The difference in clinical assessment scoring and PEFR between the montelukast group and placebo group was statistically significant (p<0.01). However at 6 months follow up symptom control in the montelukast group was not significant and the difference between the two groups was not statistically significant (p>0.05). Conclusions: Montelukast provides significant symptom control and improvement in PEFR in mild persistent asthma compared to placebo. It is effective as monotherapy in mild persistent asthma in children aged 2-12 years. Symptom control is good during therapy and until three months after discontinuation of drug.